2022
DOI: 10.3389/fmed.2022.878730
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of FGF23 on Cardiac Hypertrophy Is Not Mediated by Systemic Renin-Angiotensin- Aldosterone System in Hemodialysis

Abstract: Fibroblast growth factor 23 (FGF23) is elevated in patients with chronic kidney disease and contributes to left ventricular hypertrophy (LVH). The aim of the analysis was to determine whether this effect is mediated by the renin-angiotensin-aldosterone system (RAAS) in hemodialysis. Serum samples from 62 randomized hemodialysis patients with LVH were analyzed for plasma renin activity (PRA-S), angiotensin II (AngII), and metabolites, angiotensin-converting enzyme-2 (ACE2) and aldosterone using a high throughpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Finally, a recent clinical study showed that etelcalcetide reduces the circulating concentration of FGF23 and inhibits the progression of LVH (33). In this study, the concentration of FGF23, but not the levels of renin-angiotensin-aldosterone system (RAAS)related parameters, showed a clear association with left ventricular mass index (34).…”
Section: Fgf23 and Lvhmentioning
confidence: 52%
“…Finally, a recent clinical study showed that etelcalcetide reduces the circulating concentration of FGF23 and inhibits the progression of LVH (33). In this study, the concentration of FGF23, but not the levels of renin-angiotensin-aldosterone system (RAAS)related parameters, showed a clear association with left ventricular mass index (34).…”
Section: Fgf23 and Lvhmentioning
confidence: 52%
“…Patient characteristics at baseline are reported in Table 1 and have been described previously [ 9 , 28 , 29 ]. The degree of overhydration, assessed through body composition monitoring at the screening stage and subsequently measured at two-month intervals throughout the trial, was found to be similar between the groups [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…In line with this notion, we found unchanged renin concentrations in CPD mice, relative to mice kept on ND. However, it is unclear whether this is also true for humans because a recent study in hemodialysis patients with LVH failed to find an association between FGF23 levels and components of the RAAS [ 48 ].…”
Section: Discussionmentioning
confidence: 99%